2016
DOI: 10.1007/s00402-016-2410-3
|View full text |Cite
|
Sign up to set email alerts
|

Which factor is most important for occurrence of cutout complications in patients treated with proximal femoral nail antirotation? Retrospective analysis of 298 patients

Abstract: Althought obtaining proper tip-apex distance is important to prevent cutout complication in these fractures, if the fracture is not reduced in varus position and helical blade is inserted in the proper quadrant, possibility of cut-out complication is very low even in the patients with high tip-apex distance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 32 publications
3
64
1
4
Order By: Relevance
“…The overall complication rate in our study was 25%; it is similar to those of other authors [11,[23][24][25][26].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The overall complication rate in our study was 25%; it is similar to those of other authors [11,[23][24][25][26].…”
Section: Discussionsupporting
confidence: 92%
“…According to the literature, the cut-out of the lag screw is the most frequent complication of the nail for proximal femur fracture [11,23,[27][28][29][30][31] with an occurrence rate between 1 and 5% of surgeries [11,[23][24][25][26] causing the 84% of failures and revision surgery of these devices [32]. We found this complication in 3.7% of patients and only 4 of them occurred in group A.…”
Section: Discussionmentioning
confidence: 97%
“…From the results of our study, we observed that a TAD greater than 25 mm signi cantly increased the failure rate by using the extramedullary plate but not the intramedullary nail. Similar ndings were reported in previous reports [28][29][30]. Therefore, we postulate that the intramedullary nail provides more stability in treating unstable femoral intertrochanteric fractures than the extramedullary plate by restoring the femoral lateral wall, thus preventing the varus reduction/ xation and avoiding the medialization of the distal fragment [20,30,31].…”
Section: Discussionsupporting
confidence: 90%
“…Eine weitere Untersuchung zeigte das erhöhte Risiko für ein "cutting-out" bei reduzierter Knochendichte der Femurkopfspongiosa von < 0,6 cm 3 [14]. Besonders die unzureichende Reposition und Varusfehlstellung sind Hauptrisikofaktoren für das Implantatversagen [15]. Biomechanische Studien zeigen für die Zementaugmentationen von DHS und PFNA (AO 31-A2.3) eine signifikant höhere Stabilität im Vergleich zu den nicht augmentierten Kontrollen.…”
Section: Fraktureinteilung Und Indikationunclassified